GROWTH AND YIELDS OF Asystasia gangetica (L.) Subsp. Micrantha FERTILIZED WITH NPK WITH DIFFERENT DOSAGE - C. B. D., Carvalho; Witariadi, N. M.; Wirawan, I W. (Jurnal Peternakan Tropika; Vol 11 No 1 (2023): Vol. 11 No. 1 Tahun 2023; January - april, 2023)
This study aims to determine the growth and yield of Asystasia gangetica (L.) subsp. Micrantha fertilized with NPK with different dosage. This research was carried out in the Sesetan Research station greenhouse, Faculty of Animal Science, Udayana University starting from July to September 2021. The experimental design used in this study was a completely randomized design (CRD) with five treatments and six replications. The five treatments were dosage of 0 kg ha-1 (D0), 50 kg ha-1 (D50), 100 kg ha-1 (D100), 150 kg ha-1 (D150), and 200 kg ha-1 (D200). The variables observed in the study were growth variables, production variables, and growth characteristics variables. The results showed that treatment with different dosage of NPK fertilizer increased the dry weight of leaves, stem dry weight, total dry weight of forage, and the ratio of total dry weight of forage to root dry weight of Asystasia gangetica (L.) subsp. Micrantha, but has not had an effect on other variables. It can be concluded that the yield of Asystasia gangetica (L.) subsp. Micrantha increased with the application of NPK fertilizer, and the best results dosage of 100 kg ha-1. Keywords: Asystasia gangetica, dosage, growth, NPK, yield